Circular Economy in Agriculture: Integrating Technology for Sustainable Waste Management - Supriadi, Edi; Zulkarnaen, Adi; Suryadi; Saparuddin; Rasjid, Abdullah (GoAcademica Research & Publishing, 2025)
The agricultural sector faces significant challenges due to increasing pressure on natural resources and the need for more sustainable production systems. The linear economic model that has dominated agricultural activities has led to high levels of waste and decreased resource efficiency. In this context, implementing a circular economy is a strategic step towards creating an efficient, environmentally friendly, and competitive agricultural system. This study aims to analyze how technology integration can strengthen the implementation of a circular economy in sustainable agricultural waste management. The study used a qualitative approach, collecting data from various sources, including previous research, policy reports, and scientific publications relevant to the theme of sustainable agriculture. The data obtained were then analyzed thematically to identify the relationship between technology implementation, policy, and multi-stakeholder collaboration in supporting a circular agricultural system. The results show that transforming agricultural systems toward resource efficiency requires strong support from digital technology, adaptive public policies, and active community participation in waste management. In addition to increasing farmer productivity and welfare, a circular system also strengthens local economic resilience and environmental sustainability. Therefore, technology integration in a circular agricultural economy is a crucial pillar for realizing modern agriculture that is equitable, inclusive, and long-term resilient.